1. Not finding help here? Sign up for a free 30min tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Differentiate that equation for v(t)

  1. Nov 8, 2004 #1

    The question asks to differentiate that equation for v(t) and thus show that the acceleration is porportional to the speed at any time.

    I have no clue how to differentiate. Could someone start me off or give some clues? I'll find th rest in my text book. Thanks
  2. jcsd
  3. Nov 8, 2004 #2
  4. Nov 8, 2004 #3
    differentiate = take the derivative?

    wow...I must not be paying attention in math class
  5. Nov 8, 2004 #4
    I dont understand... the derivative of e^x = e^x?

    then the derivative of v=vi*e^(-ct) is:

    a=c*e^(-ct)+e^(-ct) * Vi?
    Last edited: Nov 8, 2004
  6. Nov 8, 2004 #5
    More like

    a = -c*vi*e^(-ct)

    Don't forget the vi.

    Now, anything in that expression look familiar? Could you fit v(t) in there somewhere?

  7. Nov 8, 2004 #6
    Where did the -c come from? Doesn't the derivative of Vi become c?
  8. Nov 8, 2004 #7
    [tex]\frac{d}{dt}v(t) = \frac{d}{dt} \left( v_i e^{-ct} \right)[/tex]

    [itex]v_i[/itex] is a constant, so

    [tex]\frac{d}{dt} v_i e^{-ct} = v_i \frac{d}{dt}e^{-ct}[/tex]

    Make a substitution u = -ct and apply the chain rule

    [tex]v_i \frac{d}{dt}e^{-ct} = v_i \left( \frac{d}{du} e^u \right) \left( \frac{du}{dt} \right) = v_i e^u \frac{d}{dt} \left( -ct \right) = v_i e^u \cdot (-c) = -c v_i e^{-ct}[/tex]

    Last edited: Nov 8, 2004
  9. Nov 8, 2004 #8
    thank you, that helps a lot. I was just wondering, my book gives an answer of a=-cv, where does the e go?
  10. Nov 8, 2004 #9
    [tex]v = v_i e^{-ct}[/tex]

    Plug v into the book's expression for a and see if it matches up with what you got. Find the e?

  11. Nov 8, 2004 #10
    [tex]v = v_i e^{-ct}[/tex]
    [tex]a = -c v_i[/tex]

    [tex]v_i e^{-ct}= -c v_i[/tex]
    [tex]e^{-ct}= -c[/tex]
  12. Nov 8, 2004 #11
    You're confusing [itex]v_i[/itex] and v(t).

    [itex]v_i[/itex] is the initial velocity, i.e. the velocity at time = 0, or v(0).

    v is the velocity as a function of time, i.e. [itex]v_i e^{-ct}[/itex], or v(t).

    Remember that [itex]v_i[/itex] is a constant.

  13. Nov 8, 2004 #12
    okay, I understand, thanks for all your help.
    Last edited: Nov 8, 2004
Know someone interested in this topic? Share this thread via Reddit, Google+, Twitter, or Facebook

Have something to add?

Similar Discussions: Differentiate that equation for v(t)
  1. V(t) and x(t) (Replies: 1)